2020
DOI: 10.1108/ajeb-06-2020-0018
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of consumers’ intention to use credit card: a perspective of multifaceted perceived risk

Abstract: Purpose The purpose of this study is to develop a theoretical model for consumer behavioral intention by integrating the technology acceptance model (TAM) and the theory of perceived risk, which is tested on the intended use of credit cards in Vietnam. Design/methodology/approach The data were collected from 485 bank customers through a nationwide online survey. An exploratory and confirmatory factor analyzes were performed to validate the factor structure of the measurement items while structural equation m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
51
0
10

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(66 citation statements)
references
References 39 publications
5
51
0
10
Order By: Relevance
“…In accordance with several literatures and previous studies which had assessed several factors which could positively affect the formation of repurchase intention within consumers' minds, it was found out that perceived ease of use, perceived security and customer satisfaction as several important factors which have a big role in affecting consumers' repurchase intention in the e-commerce environment. Perceived ease of use itself could be understood as consumers or people's perception regarding the technology or system implemented by a company, in which such perception was derived from people's believe and judgement on whether or not it will consume much time, costs or energy to the new technology or system implemented by a company (Trinh et al, 2020). In the other hand, perceived security could be defined as customers or people's perception and judgement regarding whether or not it is secure enough for customer to conduct some transactions with the company (Falk et al, 2016).…”
Section: Research Introductionmentioning
confidence: 99%
“…In accordance with several literatures and previous studies which had assessed several factors which could positively affect the formation of repurchase intention within consumers' minds, it was found out that perceived ease of use, perceived security and customer satisfaction as several important factors which have a big role in affecting consumers' repurchase intention in the e-commerce environment. Perceived ease of use itself could be understood as consumers or people's perception regarding the technology or system implemented by a company, in which such perception was derived from people's believe and judgement on whether or not it will consume much time, costs or energy to the new technology or system implemented by a company (Trinh et al, 2020). In the other hand, perceived security could be defined as customers or people's perception and judgement regarding whether or not it is secure enough for customer to conduct some transactions with the company (Falk et al, 2016).…”
Section: Research Introductionmentioning
confidence: 99%
“…Previous studies by Ariffin et al (2018) andTrinh et al (2020) had found out the significant and negative impact which was given by Security Risk on Consumers' Intention to Purchase or Adopt certain technology, in which, when consumers thought that there will be low (or even no) possibilities of consumers experiencing or suffering from any kinds of security breaches related with all of the data and personal information that consumers gave to the company, then such beliefs or perception could increase consumers' believe in the system, which eventually could increase or strengthen consumers' intention to use or adapt the system or technologies developed by the company. Furthermore…”
Section: The Effect Of Security Risk and Perceived Usefulness Toward Intention To Adoptmentioning
confidence: 95%
“…Security Risk could be defined as consumers' or people's judgment or perception regarding any kinds of possibilities that all personal judgment given by the customers to the company could be stolen in certain ways (Stocchi et al, 2019). Furthermore, Security Risk could also be understood as consumers' feelings or perceptions regarding whether or not the company could keep and ensure the safety of all personal and important data which the consumers store on the system developed by the company (Trinh et al, 2020).…”
Section: Literature Review Security Riskmentioning
confidence: 99%
See 1 more Smart Citation
“…Hence, perceived usefulness refers to the level of customers' belief in completing their purchase task through virtual stores. Past research has produced evidence that the customer's usefulness perception significantly influence customers' intention to use (Trinh et al, 2020). Further, Prakosa and Sumantika (2020) have elucidated their analysis of online shoppers' acceptance of perceived usefulness which has positively affected their attitude towards online purchase transactions.…”
Section: Factors Influencing Consumer Online Purchase Intentionmentioning
confidence: 99%